ANALISIS PERBANDINGAN KINERJA KEUANGAN PT BANK MEGA SYARIAH DENGAN PT BANK SYARIAH MANDIRI PERIODE TAHUN 2008 – 2012 - Erni Widajanti, Puput Olivia Cahyaningsih, Setyaningsih Sri Utami & (Universitas Slamet Riyadi, 2014)
The purpose of this study was to: 1) analyze the financial performance of PT Bank Mega Syariah views of the CAR, NPL, LDR, ROA and ROA. 2) Analyze the financial performance of PT Bank Mega Syariah views of the CAR, NPL, LDR, ROA and ROA. 3) Analyze significant difference financial performance of PT Bank Mega Syariah with the financial performance of PT Bank Syariah Mandiri in terms of the CAR, NPL, LDR, ROA and ROA. 4) Analyze the performance of which one is better between PT Bank Mega Syariah and PT Bank Syariah Mandiri in terms of the CAR, NPL, LDR, ROA and ROA period 2008 – 2012. The results were obtained conclusions: 1) the results showed that the NPL ratio for 5 years only in 2008 are included in the assessment criteria of healthy, while the 2009 is quite healthy, unhealthy 2010-2011, and in 2012 less healthy. 2) the financial performance of PT Bank Syariah Mandiri seen from CAR, NPL, LDR, ROA and ROA period 2008 – 2012 has been healthy